Scoping review of the literature about family-centred care with caregivers of children with cystic fibrosis - Shields, L.; Munns, Ailsa; Taylor, M.; Priddis, Lynn; Park, J.; Douglas, T. (Cambridge Publishing, 2013)
Background: Cystic fibrosis is a severe, life-shortening, inherited condition which imposes an enormous burden on the family and patient, and family-centred care (FCC) is postulated as the optimal model of care for these children and families. Aims: To search for literature investigating the use of FCC as a model of care in cystic fibrosis units for children under 13 years. Methods: A comprehensive search of the following databases was conducted: Cochrane Library, CINAHL, Embase, Medline, PsycINFO. Using the PRISMA flow chart and processes of the United Kingdom Centre for Reviews and Dissemination, we selected relevant studies. The detailed search strategies are available from the authors. We set clearly defined inclusion and exclusion criteria, and had we found any studies, we would have analysed them; however, none were found that specifically examined the topic. We decided to use this as a scoping study. Findings: One hundred and twenty-one studies were identified that met the inclusion criteria for types of studies about cystic fibrosis, but none were about FCC. Discussion: This brief report illustrates the need for research into the application of FCC as a way of caring for children and families where one or more of the children have cystic fibrosis. Implications for practice: Families of children with cystic fibrosis need supportive care in health services. Conclusions: Further research is required to explore whether or not cystic fibrosis care is family-centred, and models of care that meet the needs of all family members need to be developed, tested and used.